Depth of field and visual performance after implantation of a new hydrophobic trifocal intraocular lens - Carlos Palomino-Bautista; Alejandro Cerviño; Ricardo Cuiña-Sardiña; David Carmona-Gonzalez; Alfredo Castillo-Gomez; Ruben Sanchez-Jean (BMC Ophthalmology, 2022)
Abstract Purpose To assess the depth of field (DOF) by means of defocus curve analysis applying different visual acuity criteria in patients following cataract surgery and bilateral implantation of a new trifocal diffractive intraocular lens (IOL). Methods Fifty eyes of 25 consecutive patients who underwent implantation of the Asqelio™ trifocal IOL (AST Products Inc., USA) were enrolled in this observational prospective study. Monocular subjective DOF was obtained from defocus curves with absolute and relative criteria of tolerance for different visual acuities values. Patient’s visual satisfaction, postoperative refraction and visual acuity at far, intermediate (67 cm) and near (40 cm) distances were also measured at 1 and 3-months post-surgery. Analysis of variance was used to assess differences in refractive error after the surgical procedure, and paired t-tests were used to assess differences in VA. Patient satisfaction results were reported as percentages. Results Spherical equivalent was 0.05 ± 0.23 D and residual cylinder 0.01 ± 0.23 D 3-months after the surgery. Absolute DOF obtained was 3.29 ± 0.91 D considering 0.1 LogMAR as cut-off value, and 4.82 ± 0.69 D when 0.3 logMAR as cutoff value. Relative DOF considering a drop of 0.1 logMAR from maximum visual acuity was 2.57 ± 0.82 D, and 1.27 ± 0.70 D when a drop of 0.04 logMAR was considered. Visual acuities obtained 3-months after the surgery were 0.03 ± 0.13, − 0.05 ± 0.06, 0.03 ± 0.08 and 0.04 ± 0.08 logMAR for uncorrected and best-corrected for distance, and best distance-corrected for intermediate and near distances, respectively. Average response to visual satisfaction queries was 8.24/10 at distance, 8.04/10 at intermediate, and 7.88/10 at near. Conclusions Patients implanted with this trifocal IOL showed a significant improvement in visual acuity at different distances providing wide absolute and relative DOF values. The outcomes demonstrate that this lens is predictable yielding good patient satisfaction rates.